Bullying within the Forestry Organizations of Turkey - Devlet Toksoy; Mahmut Muhammet Bayramoğlu (The Scientific World Journal)
Today, many studies are conducted in order to determine bullying behaviors and to resolve conflicts with the purpose of increasing and maintaining organizational success in developed countries. According to these studies, bullying cases are more common in public institutions when compared to other sectors. In public institutions, bullying generally occurs when successful workers are discouraged and/or harassed by their managers, thus leaving them feeling distressed and dissatisfied with their jobs. The present study examines whether forest engineers working in the seven geographical regions of Turkey are exposed to bullying behaviors, the level of any bullying, and whether there are any regional differences (N=835). Through statistical analysis, a significant relationship was determined between bullying and demographic characteristics. The results of the present study were evaluated along with the results of other studies, and some suggestions were made in order to prevent bullying behaviors in forestry organizations.